A dynamic network analysis of the information flows during the management of a railway disruption - Schipper, Danny; Gerrits, Lasse; Koppenjan, Joop F.M. (European Journal of Transport and Infrastructure Research, 2015)
Railway systems experience disruptions on a daily basis. We test the use of Dynamic Network Analysis as a methodological tool in order to investigate the communication patterns during the dynamic process of disruption management. The tool was applied to a simulated case of a catenary failure in the Dutch railway system. DNA provides a systematic overview of the communication patterns and tasks associated with the disruption management process. Key actors were identified and the overall structure of the network analyzed. The dynamic component to our network analysis revealed that information is being shared within disconnected parts of the network during the first few minutes, without those parts having a direct link to the source of the information. These findings show that employing only static analysis of networks obscures the real dynamics of information sharing during railway disruptions and potential coordination problems. DNA therefore can be an important method and tool to reveal issues that need to be resolved.